2006
DOI: 10.1007/s11248-006-9020-8
|View full text |Cite
|
Sign up to set email alerts
|

Production of endothelial nitric oxide synthase (eNOS) over-expressing piglets

Abstract: Vascular function, vascular structure, and homeostasis are thought to be regulated in part by nitric oxide (NO) released by endothelial cell nitric oxide synthase (eNOS), and NO released by eNOS plays an important role in modulating metabolism of skeletal and cardiac muscle in health and disease. The pig is an optimal model for human diseases because of the large number of important similarities between the genomic, metabolic and cardiovascular systems of pigs and humans. To gain a better understanding of card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 64 publications
0
30
1
1
Order By: Relevance
“…It has been reported that NO has a regulatory role in several processes, including ovulation, regression of the corpus luteum, and early embryonic development (8). In the present study, while eNOS expression was not observed in the epithelium of either the ampulla or the fimbria during both the oestrus and luteal phases, in the oestrus phase, strong eNOS expression was determined in both the epithelial and endothelial cells of the isthmus.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…It has been reported that NO has a regulatory role in several processes, including ovulation, regression of the corpus luteum, and early embryonic development (8). In the present study, while eNOS expression was not observed in the epithelium of either the ampulla or the fimbria during both the oestrus and luteal phases, in the oestrus phase, strong eNOS expression was determined in both the epithelial and endothelial cells of the isthmus.…”
Section: Discussioncontrasting
confidence: 49%
“…It has been indicated that NO plays a regulatory role in multiple processes, including the secretion of gonadotropins, ovulation, regression of the corpus luteum, and early embryonic development. Furthermore, it has been stated that NO produced by blood vessel endothelium and oviduct epithelium has a regulatory role in the production of the oviduct fluid (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the use of pigs as experimental animals is concerned, miniature pigs are smaller and easier to handle than common domestic pigs, and they have been used in a variety of fields, such as medical and pharmacological research [10,[18][19][20][21][22][23][24][25]. However, compared with common domestic pigs, far less information regarding the production of cloned and genetically modified pigs is available for miniature pigs [10,13,14,[26][27][28][29][30][31].In the present study, we conducted a series of experiments including (i) validation of an estrus synchronization procedure for miniature pig recipients, (ii) examination of the developmental competence of nuclear transfer embryos reconstructed with various nuclear donor cells and (iii) comparison of miniature pigs and common domestic pigs as recipients. The results indicate that it is possible to produce cloned miniature pigs using common domestic pigs as the recipients and to produce genetically modified-cloned miniature pigs with a level of efficiency comparable to that for conventionally cloned miniature pigs.…”
mentioning
confidence: 99%
“…Already, α1,3-galactosyltransferase gene knockout pigs have been produced as organ donors for xenotransplantation [1][2][3][4][5][6][7][8]. In addition, transgenic pigs serving as human disease models, such as those carrying the gene for endothelial cell nitric oxide synthase (eNOS), have been developed [9]. To further advance the use of cloned and genetically modified pigs in research, however, a SCNT system that enables more efficient generation of embryos is needed.…”
mentioning
confidence: 99%